Black Metal: A Critical Analysis - Mohd Asri Bin Abd. Wahab (Universiti Sains Islam Malaysia, 2022)
Many parties were worried about the social problems that happened among the Malaysian Society. In this case, I choose, as a topic of my Academic Writing is the Black Metal Problem. I hope that this will contribute some information regarding the dangerous of the Black Metal to the Malaysian Society. Then, using the Interview, Questionnaire and Library Research Methods. This Academic Writing Project has been conducted. The Library references are including the Internet, book, Magazine and some paperwork's. As a result for this research it has been found that most of the Malaysian Youth really like this type of Heavy Metal music. Which me lodes those of the school age adolescents. Particularly to the Muslim as this movement can cause a bad impact for the Islamic creed of one.